ANALYSIS OF CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN KEDAI COFFEE (Case Study of SMEs in Jakarta Indonesia) - Hudaya, Agung (Dinasti Publisher, 2020)
The purpose of this study is to find out how product quality, price, customer satisfaction on customer loyalty and how much influence the product quality, price, on customer satisfaction has implications for customer loyalty. This study is a census, the number of objects in the population with 100 respondents. The research method used in this research is descriptive analysis method. Data analysis techniques used are correlation analysis techniques and SEM (structural equation model) analysis techniques. Correlation analysis techniques to determine the relationship between variables, while SEM analysis techniques to determine how much influence the independent variable has on the dependent variable. The software used to process and analyze data from this study is Smart PLS version 3.0.